DBXplorer: Enabling Keyword Search over Relational Databases - Agrawal, Sanjay; Chaudhuri, Surajit; Das, Gautam (ACM SIGMOD 2002, 2002)
Internet search engines have popularized keyword based search. While relational database systems offer powerful structured query languages such as SQL, there is no support for keyword search over databases. The simplicity of keyword search as a querying paradigm offers compelling values for data exploration. Specifically, keyword search does not require a priori knowledge of the schema. The above is significant as much information in a corporation is increasingly being available at its intranet. However, it is unrealistic to expect users who would browse and query such information to have detailed knowledge of the schema of available databases. Therefore, just as keyword search and classification hierarchies complement each other for document search, keyword search over databases can be effective.